Lives in music : mobility and change in a global context - Le Menestrel, Sara; Apprill, Christophe; Argyriadis, Kali; Mallet, Julien; Puig, Nicolas; Samson, Guillaume; Segré, Gabriel (Routledge studies in ethnomusicology, 2020)
Lives in music analyses interwoven patterns of mobility, change, and power in music and dance practices. It challenges some commonly accepted conceptual tools that are ubiquitous in anthropology today, including cultural hybridity, transnational networks, and globalization. Based on seven itineraries that are the result of extensive ethnographic long-term field research efforts, the processes of geographic and social mobility, transformation, and power relative to music and dance practices are explored in different parts of the world. Seven writers provide itineraries constructed through ethnographic techniques and life histories and supported by a deep knowledge of local customs.